Effects of human trampling on populations of soil fauna in the McMurdo Dry Valleys, Antarctica - Ayres, E.; Nkem, J.; Wall, D.H.; Adams, B.J.; Barrett, J.E; Broos, E.J.; Parson, A.N.; Powers, L.E.; Simmons, B.L.; Virginia, R.A. (2008)
Antarctic ecosystems are often considered nearly pristine because levels of anthropogenic disturbance are extremely low there. Nevertheless, over recent decades there has been a rapid increase in the number of people, researchers and tourists, visiting Antarctica. We evaluated, over 10 years, the direct impact of foot traffic on the abundance of soil animals and soil properties in Taylor Valley within the McMurdo Dry Valleys region of Antarctica. We compared soils from minimally disturbed areas with soils from nearby paths that received intermediate and high levels of human foot traffic (i.e., up to approximately 80 passes per year). The nematodes Scottnema lindsayae and Eudorylaimus sp. were the most commonly found animal species, whereas rotifers and tardigrades were found only occasionally. On the highly trampled footpaths, abundance of S. lindsayae and Eudorylaimus sp. was up to 52 and 76% lower, respectively, than in untrampled areas. Moreover, reduction in S. lindsayae abundance was more pronounced after 10 years than 2 years and in the surface soil than in the deeper soil, presumably because of the longer period of disturbance and the greater level of physical disturbance experienced by the surface soil. The ratio of living to dead Eudorylaimus sp. also declined with increased trampling intensity, which is indicative of increased mortality or reduced fecundity. At one site there was evidence that high levels of trampling reduced soil CO2 fluxes, which is related to total biological activity in the soil. Our results show that even low levels of human traffic can significantly affect soil biota in this ecosystem and may alter ecosystem processes, such as carbon cycling. Consequently, management and conservation plans for Antarctic soils should consider th e high sensitivity of soil fauna to physical disturbance as human presence in this ecosystem increases.